The Effect of Shoe Insole Stiffness on Leg Stiffness during Stance Phase of Running in Two Different Speeds ‎among Active Men - Zeinab Tazike-Lemeski; Mansour Eslami; Fereshteh Habibi-Tirtashi (Vesnu Publications, 2016)
Introduction: The effect of shoe insoles with different characteristics and in different running speeds on lower-limb stiffness is still ‎controversial. The aim of this study was to investigate the effect of two types of insoles (soft and semi-rigid) in two ‎different running speeds on leg stiffness during stance phase of running among active men.‎ Materials and Methods: ‎15 male students without any background of lower extremity injury were selected. Subjects were asked to run with ‎two controlled velocities of 3.0 ± 0.2 and 5.0 ± 0.1 m/s in control and insole conditions (soft and semi-rigid) on a ‎force plate, placed on the middle of 15-meter runway. The cinematics and cinetics of motion were measured and ‎calculated using 5 video cameras and one force plate. The leg stiffness was achieved via dividing the vertical ‎ground reaction force by leg compression. Two-factor repeated measures ANOVA was used to test the hypothesis at ‎the significance level of P £ 0.050.‎ Results: There was a significant difference between the two types of insoles on leg stiffness. In fact, semi-rigid insole significantly increased leg stiffness (P < 0.001). However, this discrepancy was not related to the running speed (P = 0.999). In addition, there was no significant difference between the two different speeds on leg stiffness (P = 0.632). Conclusion: It seems that the increase in shoe insole stiffness may increase the leg stiffness. Furthermore, the effect of insole ‎stiffness is not related to the running speed, and leg stiffness will remains constant in low to medium running speeds.‎